Phenomenological Studies in Reforming Smart Buildings According to the Community Concept 5.0 - Donatus Ara Kian; LMF Purwanto (Architectural Research Journal, 2021)
Today, with the various problems faced by the world community, it requires everyone in various countries to develop technology and science to overcome various problems that are currently faced and predict future problems. Through innovation, the world's technological engineering is felt in the palm of the hand, even if only by means of a cell phone. This condition then inspired the Japanese Cabinet in 2016 to initiate society 5.0 or Society 5.0 through the Japanese Cabinet within the framework of the 5th Science and Technology Basic Plan. The big vision carried by the Japanese Cabinet in the 5th design and technology plan is to create a Super Intelligent Society (MSC). MSC is positioned as the fifth stage of development in the social structure of society, after previously the hunter / gatherer, agrarian, industrial, and information societies. In line with the development and innovation referred to above, the demand for services in the property sector, especially in building buildings, is getting higher. So that the concept of "Smart Building" or better known as Smart Building / Intelligent Building is created. This concept was born as a result of increasing human welfare and changes in modern life patterns that demand a level of service and management of the building environment, which greatly affects the welfare and services in the workplace, which in turn will affect productivity, morality and satisfaction. Therefore, efforts to adjust the current conditions between the speed of information technology development and the growth of a new generation of humans in this era which are almost linear / concurrent, as well as between society and building, are an effort that must be made so that technological and social developments can coincide. . This effort is what is meant by reformulation of Smart Buildings in the Concept of Society 5.0.